Pengaruh Filsafat Positivisme Dalam Pengembangan Kurikulum Pendidikan Agama Islam - Ghina Ulpah; Irawan Irawan; Tedi Priatna; Kemal Al Kautsar Mabruri; Muhtadin Muhtadin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Islamic religious education curriculum is an important component of the education system in countries with a majority Muslim population. It should reflect Islamic principles, but also incorporate modern elements to meet the broader demands of education. In this regard, the philosophy of positivism has played an important role in the development of the Islamic religious education curriculum. This research aims to outline the influence of positivism in the development of Islamic religious education curriculum, and discuss the implications and challenges that may arise. This research uses a qualitative method with a literature study taken from various sources, both print and electronic media, books and electronic journals. There are primary and secondary sources in the form of published scientific works with a high credibility index. data analysis is taken from a literature review by means of researchers collecting data, and complete information from various data collection procedures and with a specified time. The data collected is analyzed using descriptive methods to reveal the facts of the incident written in statements derived from the data sources studied. All data obtained related to the philosophy of positivism and science, the Islamic education curriculum is collected and analyzed which is then associated with its role in the development of the Islamic education curriculum so as to produce a description in accordance with the purpose of writing this article. In conclusion, the influence of positivism philosophy in the development of Islamic education curriculum has brought benefits in pursuing a more rational and evidence-based education. However, it should be kept in mind that religious values and spiritual aspects should also remain a focus in the development of this curriculum. A balance between the positivistic approach and religious values is the key to achieving a comprehensive and relevant Islamic religious education.